Nonlinear Almost Contractions of Pant Type Under Binary Relations with an Application to Boundary Value Problems - Esmail Alshaban; Adel Alatawi; Fahad M. Alamrani; Ahmed Alamer; Naif N. Alrshidi; Faizan Ahmad Khan (Mathematics)
In this article, we prove certain fixed point findings for a nonlinear almost contraction map of the Pant type in a metric space endowed with a binary relation. The outcomes presented here expand, develop, enhance, and consolidate several existing findings. With a view to arguing for our findings, we furnish a few examples. As an application of our outcomes, we discuss the existence of a unique solution of a boundary value problem of the first order.